Zagadnienie aksjologicznej deskrypcji żalu w języku rosyjskim - Николаенко, Лариса (Studia Rossica Posnaniensia, 2017)
The author argues that the Russian language world-view verbalizes a dual assessment of pity. Moral assessment of pity as the soul's immediate response to someone else's suffering is positive. However, the uncomfortable and even painful process of experiencing this emotion and the high degree of intensity of its influence on one's psyche results in a negative hedonic evaluation of pity. This explains the metaphorical conceptualization of pity in images of pain, aggressive power, water element, and fire.